The Role of Social Media in Shaping Trendy Beverage Consumption in the Café Industry - Meli Rista Angrraini Angrraini; Risckha Nurcahyani; Risnawati Risnawati (Journal Hotspot, 2026)
This study aims to analyze the role of social media in shaping trendy beverage consumption in the café industry. This research employs a quantitative approach using correlation and regression analysis to examine the relationship between social media variables and consumption trends. The sample in this study consisted of 100 respondents who are consumers of The Well Belitung, OS Kongdjie, and Happy Resto. The theory applied in this study is the Diffusion of Innovations, which explains how an innovation can spread and be adopted by society through social media. The results indicate that social media has a positive and significant influence on trendy beverage consumption. The higher the intensity and quality of content presented on social media, the greater its impact on shaping consumer preferences and purchasing decisions. In conclusion, social media plays an important role in creating and strengthening consumption trends. Therefore, café business owners are encouraged to optimize social media as an effective marketing strategy that aligns with the characteristics of their target market, particularly Generation Z.